The Association Between Age and Parity with the Incidence of Cervical Cancer: A Case-Control Study - Susilawati Susilawati; Nasywa Ardelia Putri; Ana Mariza; Sunarsih Sunarsih (Poltekkes Kemenkes Palu, 2025)
Background: Cervical cancer is one of the leading causes of mortality among women worldwide and ranks second in Indonesia after breast cancer. Data from Dr. H. Abdul Moeloek General Hospital in 2024 recorded 255 hospitalized patients diagnosed with cervical cancer, equivalent to approximately 0.57% of total visits. Risk factors associated with cervical cancer incidence include age and parity, which may influence susceptibility to persistent HPV infection and cervical cell changes. Methods: This study employed a quantitative case-control design. The study population consisted of all 255 inpatients diagnosed with cervical cancer in 2024. A total of 192 respondents were selected using random sampling, comprising 96 cases (with cervical cancer) and 96 controls (without cervical cancer). Data were analyzed using univariate and bivariate methods with the Chi-Square test. Results: The Chi Square test results show a significant relationship between age and cervical cancer incidence (p=0.001; OR=44.922), as well as a relationship between parity and cervical cancer incidence (p=0.001; OR=103.400). Women who are older and have higher parity are at greater risk of developing cervical cancer than those who are at lower risk. Conclusion: There is a significant association between age <20/>35 years and grandmultiparity with the incidence of cervical cancer. Women of reproductive age are advised to increase their awareness of early detection through regular IVA (Visual Inspection with Acetic Acid) or Pap smear examinations at least every 3 years. Health workers are expected to strengthen health promotion programs on healthy reproductive age and safe number of births in order to reduce the incidence of cervical cancer.